Cosmopolitan Intimacies: Malay Film Music of the Independence Era, by Adil Johan - Ahmad Fuad Rahmat, (Kajian Malaysia, 2018)
The ambitious richness of Adil Johan's Cosmopolitan Intimacies will see it become an influential text for various disciplines. Interdisciplinary in approach, drawing from history, sociology and ethnomusicology, while masterfully narrating a historical big picture with careful attention to detail, it will undoubtedly serve as an indispensable resource for further inquiries into modernity and the future of Malaysian identity and cosmopolitanism more broadly